Chemical Composition and Antibacterial Activity of Essential Oil from Leaves of Justicia adhatoda Against Methicillian Resistant and Sensitive Strain Along with Their Clinical Isolates. Issue 1 (2nd January 2017) - Shukla, Shipra; Hegde, Satisha; Kumar, Anil; Chaudhary, Gaurav; Tewari, S.K.; Upreti, D.K.; Pal, Mahesh
Abstract: Higher and aromatics plants have traditionally been used in folk medicine as well as to extend the shelf life of foods, showing inhibition against bacteria, fungi and yeasts. Most of their properties are due to essential oils produced by their secondary metabolism. Essential oils and extracts from several plant species are able to control microorganisms related to skin, dental caries, and food spoilage, including Gramnegative and Gram-positive bacteria. The present study is based on the evaluation of antimicrobial activity of the essential oil of the fresh leaves of Justicia adhatoda and to identify the chemical constituents responsible for antimicrobial potential. The chemical constituents of essential oil were identified by gas chromatographymass spectrometry (GC-MS).The essential oil was evaluated for the antimicrobial potential against methicillin resistant and sensitive Staphylococcus aureus along with its clinical isolates. GC-MS analysis revealed that the major constituents of the essential oil were phytol (57.8 %), n-hentriacontane (3.92 %), nonacosane (3.65 %), pentacosane (2.65 %), β-Eudesmol (1.14 %), heneicosane (1.13 %). Result indicates that J. adhatoda leaves essential oil has a strong antimicrobial activity against mentioned microorganisms (MIC: 62.5–250 μg/mL).